The trajectory of egress in a fashion course: curriculum and professional performance (ModaPalavra e-periódico, 2020)
This research aimed to understand the trajectory of thegraduates of the first class of the fashion course of a publicuniversity. With this purpose we analyze the curriculumrelations of the initial formation and the fields of action of thegraduates fromthe formative course. Documents from theCourse Feasibility Project (1996) and the graduatesquestionnaires (2001) were analyzed from the thematicanalysis of Bardin (2016). The results demonstrate thetechnical characteristics of the curriculum due to the practicalcontext of the regional industrial clothing industry. Regardingthe graduation course of the graduates demonstrated updateto the Fashion market acting in intellectual fields between theservice industry, industry and MEI.
Keywords: ashion curriculum; graduates; professional performance